Gobies of the British Isles (Teleostei: Gobioidei) - Peter, Miller (Frontiers in Marine Science, 2015)
The marine and estuarine fishes of the British Isles currently include 17 species of gobioid percomorphs. The criteria for recognising these, apart from external features, involve the skeleton and the male genitalia, and all are goby-grade, the most speciose and varied of three main structural grades in the Gobioidei. The typical goby pelvic disc, formed by fusion of the paired pelvic fins and completed with a tranverse anterior membrane, is illustrated and distinction made between the generalised condition of separate pelvics and those gobiid pelvic fins that are secondarily separated. British gobies are divisible into four categories, two 'gobiine' and two 'gobionelline', using patterns of head lateral-line canals and free neuromast organs, as well as first dorsal fin pterygiophore sequence and number of vertebrae. These are the gobiines with the Gobius group comprising six Gobius species and one Thorogobius, and the single 'longitudinal' gobiine Lesueurigobius, the subject of another presentation. The British gobionellines comprise the sand-gobies, with five confirmed Pomatoschistus species, one each of Gobiusculus and Buenia, and two of Lebetus. The other gobinellines are two aphiine progenetic species placed in Aphia and Crystallogobius respectively. In conclusion, the British gobiines are illustrated with brief notes on size, habitat, and distribution.